Development and evaluation of an inclined draper - BEENA GEORGE L DEEPU D. S KARTHIKA KAIMAL; Dr. Sudheer K. P (Guide) (Tavanur 2003 Kelappaji College of Agricultural Engineering and Technology)
inclined draper for cleaning and separating grains . KCAET product. the machine consists two rollers, a rubber belt ...
Development and evaluation of an inclined draper